In Vitro Prebiotic Effects and Antibacterial Activity of Five Leguminous Honeys - Florinda Fratianni; Beatrice De Giulio; Antonio d’Acierno; Giuseppe Amato; Vincenzo De Feo; Raffaele Coppola; Filomena Nazzaro (Foods, 2023)
Honey is a natural remedy for various health conditions. It exhibits a prebiotic effect on the gut microbiome, including lactobacilli, essential for maintaining gut health and regulating the im-mune system. In addition, monofloral honey can show peculiar therapeutic properties. We in-vestigated some legumes honey’s prebiotic properties and potential antimicrobial action against different pathogens. We assessed the prebiotic potentiality of honey by evaluating the antioxidant activity, the growth, and the in vitro adhesion of Lacticaseibacillus casei, Lactobacillus gasseri, Lacticaseibacillus paracasei subsp. paracasei, Lactiplantibacillus plantarum, and Lacticaseibacillus rhamnosus intact cells. We also tested the honey’s capacity to inhibit or limit the biofilm produced by five pathogenic strains. Finally, we assessed the anti-biofilm activity of the growth medium of probiotics cultured with honey as an energy source. Most probiotics increased their growth or the in vitro adhesion ability to 84.13% and 48.67%, respectively. Overall, alfalfa honey best influenced the probiotic strains’ growth and in vitro adhesion properties. Their radical-scavenging activity arrived at 83.7%. All types of honey increased the antioxidant activity of the probiotic cells, except for the less sensitive L. plantarum. Except for a few cases, we observed a bio-film-inhibitory action of all legumes’ honey, with percentages up to 81.71%. Carob honey was the most effective in inhibiting the biofilm of Escherichia coli, Listeria monocytogenes, Pseudomonas aeruginosa, and Staphylococcus aureus; it retained almost entirely the ability to act against the bio-film of E. coli, L. monocytogenes, and S. aureus also when added to the bacterial growth medium instead of glucose. On the other hand, alfalfa and astragalus honey exhibited greater efficacy in acting against the biofilm of Acinetobacter baumannii. Indigo honey, whose biofilm-inhibitory action was fragile per se, was very effective when we added it to the culture broth of L. casei, whose supernatant exhibited an anti-biofilm activity against all the pathogenic strains tested. Conclusions: the five kinds of honey in different ways can improve some prebiotic properties and have an inhibitory biofilm effect when consumed.